Epidemiological and clinical characteristics of 333 confirmed cases with coronavirus disease 2019 in Shanghai, China. Issue 4 (13th May 2020) - Yu, Xiao; Sun, Xiaodong; Cui, Peng; Pan, Hao; Lin, Sheng; Han, Ruobing; Jiang, Chenyan; Fang, Qiwen; Kong, Dechuan; Zhu, Yiyi; Zheng, Yaxu; Gong, Xiaohuan; et al.
Abstract: Coronavirus disease 2019 (COVID‐19) is an emerging infectious disease first identified in Wuhan City, Hubei Province, China. As of 19 February 2020,  there had been 333 confirmed cases reported in Shanghai, China. This study elaborates on the epidemiological and clinical characteristics of COVID‐19 based on a descriptive study of the 333 patients infected with COVID‐19 in Shanghai for the purpose of probing into this new disease and providing reference. Among the 333 confirmed cases in Shanghai, 172 (51.7%) were males and 161 (48.3%) were females, with a median age of 50 years. 299 (89.8%) cases presented mild symptoms. 139 (41.7%) and 111 (33.3%) cases were infected in Wuhan and Shanghai, respectively. 148 (44.4%) cases once had contact with confirmed cases before onset, while 103 (30.9%) cases had never contacted confirmed cases but they had a sojourn history in Wuhan. The onset date of the first case in Shanghai was 28 December, with the peak appearing on 27 January. The median incubation period of COVID‐19 was estimated to be 7.2 days. 207 (62.2%) cases had fever symptoms at the onset, whereas 273 (82.0%) cases experienced fever before hospitalization. 56 (18.6%) adults experienced a decrease in white blood cell and 84 (42.9%) had increased C‐reactive protein after onset. Elderly, male and heart disease history were risk factors for severe or critical pneumonia. These findings suggest that most cases experienced fever symptoms and had mild pneumonia. Strengthening the health management of elderly men, especially those with underlying diseases, may help reduce the incidence of severe and critical pneumonia. Time intervals from onset to visit, hospitalization and diagnosis confirmed were all shortened after Shanghai's first‐level public health emergency response. Shanghai's experience proves that COVID‐19 can be controlled well in megacities.